FROM CULT CLASSIC TO MODERN HORROR: THE PLOT TRANSFORMATION OF PENGABDI SETAN (1980) AND PENGABDI SETAN (2017) - Paradita, Zahra Intan; Haq, Maulaya Arinil; Fitriana, Alviatum Rizqi Eka; Amin, Ahmad Mutawakkil; Oktaviandini, Rachelina Nisa; Kausch II, Christopher J. (CrossOver, 2025)
To make the story of a movie relevant each year, movie producers try to remake their work into a new story that is relevant with the perspective of the people to attract a more comprehensive audience. Thus, to make the remake movie more relevant to audience development, producers occasionally need to change the narrative from hypotext (source) to hypertext (new adaptation). This research aims to analyze the narrative from plot transformation of the films Pengabdi Setan (1980) and Pengabdi Setan (2017). The study focuses on the changes in the plot of the movie Pengabdi Setan (2017), adapted from the film with the same title in 1980. This qualitative research is analyzed using both narrative transformation with plot as the focus in this study and Transtextuality, as conceptualized by Gerard Genette, which divides narrative transformation into four types: Transdiegetization, Transpragmatization, Transmotivation, and Transvaluation and divides Transtextuality into two types mainly augmentation and reduction to analyze the plot transformation between the source story and its remake, Pengabdi Setan (1980) into its remake movie, Pengabdi Setan (2017). Narrative transformation, especially plot transformation, using Freytag’s Pyramid that divides dramatic elements of a story into five parts, including exposition, rising action, climax, falling action, and resolution. The data are collected by watching and documenting the plot differences and then using Miles and Huberman (1994) for analyzing the data. The analysis reveals significant transformations in the plot of the remake movie, primarily through the strategies of reduction and augmentation. It is shown that augmentation is the most predominant strategy used in the Pengabdi Setan (2017), effectively transforming and elevating the plot while retaining the essence of the original story.